The Book of the Twelve: composition, reception, and interpretation - Tiemeyer, Lena-Sofia; Wöhrle, Jakob (Vetus Testamentum / Supplements, 2020)
"In the last two decades, research on the Book of the Twelve has shown that this corpus is not just a collection of twelve prophetic books. It is rather a coherent work with a common history of formation and, based upon this, with an overall message and intention. The individual books of the Book of the Twelve are thus part of a larger whole in which they can be interpreted in a fruitful manner. The volume The Book of the Twelve: Composition, Reception, and Interpretation features 30 articles, written by renowned scholars, that explore different aspects regarding the formation, interpretation, and reception of the Book of the Twelve as a literary unity"--